Vpliv pridruženih bolezni na zmožnost hoje s protezo po amputaciji spodnjega uda - Saksida, Ana (Rehabilitacija (Ljubljana), 2024)
Background: Most lower limb amputations are due to peripheral vascular disease, and are performed in elderly patients, who often have multiple comorbidities that can negatively affect their physical and mental abilities, in turn affecting their ability to walk with a prosthesis. The aim of our research was to determine the relationship between the number of comorbidities, assessed by the Functional Comorbidity Index (FCI) value, and the functional outcome of rehabilitation, defined as successful use of prosthesis after a lower limb amputation. Methods: We included 216 patients who underwent primary rehabilitation after lower limb amputation in 2019. The FCI values were compared according to the age of the patients, the level of amputation and according to whether or not a prosthesis was prescribed by the end of the rehabilitation. Results: In the majority of patients (83 %), the cause of amputation was vascular disease (PAD or a complication of diabetes). The most common comorbidity in patients was arterial hypertension (73 %), followed by diabetes (57 %) and PAD (53 %). The mean FCI value was 3.1; the value increased with age, indicating that older patients have a greater number of comorbidities. No significant differences in the mean FCI value was observed according to the level of amputation. A statistically significantly higher FCI value was found in patients who were not prescribed with a prosthesis than in patients who received a prosthesis by the end of the rehabilitation. Conclusions: By using the FCI, we showed that a greater number of comorbidities is associated with a poorer rehabilitation outcome after a lower limb amputation.
Keywords: amputacija; amputation; comorbidity; FCI; Functional Comorbidity Index; funkcijski indek soobolevnosti; Gait; hoja; lower limb; Multiple Amputations, Traumatic; pridružene bolezni; prosthesis; proteza; rehabilitation; spodnji ud; walking